DIFFERENTIATED EDUCATION IN SCHOOL OF PEDAGOGICAL PROFESSIONALISM AS ONE OF WAYS OF PREPARING BEGINNING TEACHERS PEDAGOGICAL PROCESS MANAGEMENT - H.B. Shtelmakh (Academy of Cognitive and Natural Sciences, 2003)
For the formation of the artistic personality of the teacher there must be clone a systematical work on the perfection of his personal professional significant features. This problem can be sold by means of the organization of the teaching activity of the teachers - beginners at school of the pedagogical professionalism during the involvement into the active pedagogical activity, into the different kids of different training. The active forms and methods of teaching have great possibilities in the process of solving this problem.